2021
DOI: 10.3390/medicina57060522
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Induction as a Host-Directed Therapeutic Strategy against Mycobacterium tuberculosis Infection

Abstract: Tuberculosis (TB), a bacterialinfectious disease caused by Mycobacterium tuberculosis (M.tb), which causes significant mortality in humans worldwide. Current treatment regimen involve the administration of multiple antibiotics over the course of several months that contributes to patient non-compliance leading to relapse and the development of drug-resistant M.tb (MDR and XDR) strains. Together, these facts highlight the need for the development of shorter TB treatment regimens. Host-directed therapy (HDT) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 167 publications
0
7
0
Order By: Relevance
“…CALCOCO2 plays a similar role in that it functions as a receptor for ubiquitin-coated bacteria and plays an important role in innate immunity by mediating macro-autophagy (52)(53)(54). This suggests a role in targeting TB bacilli for degradation by the innate immune system (54)(55)(56), which TB has evolved strategies to evade (57,58). However, increased CALCOCO2 expression may be a double-edged sword as it also targets the signalling adaptor MAVS for ubiquitination and autophagic degradation, hence inhibiting DDX58-mediated type I interferon signalling through a negative feedback loop (59).…”
Section: Discussionmentioning
confidence: 99%
“…CALCOCO2 plays a similar role in that it functions as a receptor for ubiquitin-coated bacteria and plays an important role in innate immunity by mediating macro-autophagy (52)(53)(54). This suggests a role in targeting TB bacilli for degradation by the innate immune system (54)(55)(56), which TB has evolved strategies to evade (57,58). However, increased CALCOCO2 expression may be a double-edged sword as it also targets the signalling adaptor MAVS for ubiquitination and autophagic degradation, hence inhibiting DDX58-mediated type I interferon signalling through a negative feedback loop (59).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, studies have shown that enhancing phagocytosis can effectively limit the intracellular growth of Mtb 343,344 . Phagocytosis serves as the fundamental link between the innate and adaptive branches of the immune system 345 .…”
Section: Host‐directed Therapymentioning
confidence: 99%
“…Trehalose is a naturally occurring disaccharide composed of two D-glucose molecules connected by glycosidic linkage, with the α, α-1,1-trehalose form being the most common in living organisms ( Adikesavalu et al, 2021 , Vanaporn and Titball, 2020 ). Trehalose is a vital carbon source for many bacteria and can support bacterial development; therefore, it plays a crucial function in protecting bacteria from various stressors ( Vanaporn and Titball, 2020 ).…”
Section: Autophagy Induction As Host-directed Tb Therapymentioning
confidence: 99%